Engineering thermodynamics of thermal radiation for solar power utilization - Petela, Ryszard, 1933- (McGraw-Hill's AccessEngineering., 2010)
This comprehensive guide reviews the fundamentals of the thermodynamics of radiation matter--photon gas. The book introduces the exergy of radiation through the most advanced thermodynamic analysis of the solar power processes involving radiation. Engineering Thermodynamics of Thermal Radiation: For Solar Power Utilization provides, for the first time, an exhaustive discussion on energy and exergy analysis of radiation processes. Extensive details on the exergy of radiation are developed for evaluation of the practical uses of radiation. This volume contains quantitative calculation examples for solar heating, a solar chimney power plant, photosynthesis, and photovoltaic technology. Addressed to researchers, designers, and users of different solar installations, the book also has the potential to inspire the development of new applications of radiation exergy. -- Back cover.